The Trust Ladder and Social Capital as a Basis for the Strategic Management of Companies in the Twenty First Century - Leśniak-Łebkowska, Grażyna (Studia Oeconomica Posnaniensia, 2017)
Dynamic changes of the contemporary environment, the increasing economic activity of competing companies, and the potential of organizations leading the economic consolidation within their business ecosystems allow them to act on a large scale and create immense impacts. It calls for a reflection on the durability of this success. Due to the digital revolution, new manufacturing technologies and innovations in products, processes and business models new revenue streams appear together with new lifestyles reflecting the phenomenon called the 'new economy'. These changes are built on trust and social capital shaping human relationships and the propensity to cooperate. Both undergo diverse impacts, which are both positive and negative. The trust ladder is a metaphor illustrating the multi-stage process of building positive supplier-client relationships. Social capital and its re-investment in new areas create a favourable climate for long-term business development. The metaphor of the value creation ladder in strategic management corresponds with the trust ladder and enables the analysis of existing states as well as future developments.